Seroprevalance of toxoplasmosis on stray dogs in elazığ - Münir Aktaş; Cahit Babür; Zafer Karaer; Nazir Dumanlı; Ergün Köroğlu (Eurasian Journal of Veterinary Sciences)
This study was carried out in stray dogs in Elazığ. A total of 53 dogs were examined for the presence of anti-Toxoplasma gondii antibodies using Sabin-Feldman test (SF). Anti-Toxoplasma gondii antibodies were detected in 40 (75.4%) of the dogs. Titers of 1/16, 1/64, 1/256, 1/1024 were found in 17 (42.5%), 12 (30%), 8 (20%) and 3 (7.5%) of the seropositive dogs respectively.